Influence of Spherical and Pyramidical Dimples and Bumps on Airfoil Performance in Subsonic Flow - Mehtar,Zahra (2021)
ABSTRACT In this study, surface features such as dimples and bumps are introduced to the surface of a NACA 0012 airfoil to study their effect on boundary layer separation, particularly at high angles of attack. Six modified airfoils were designed with dimples and bumps of spherical and pyramidical shapes. A computational fluid dynamics (CFD) analysis was conducted on these models at subsonic flow using Ansys Fluent. The analysis used the Shear Stress Transport k – ω turbulence model at a varying angle of attack (AOA) from 0 to 15°. The velocity contours and streamlines were generated. Also, the lift coefficient, drag coefficient and the lift-to-drag performance ratio were computed and analyzed. The results showed that all surface modifications led to delayed flow separation and flow recirculation. All surface modification also resulted in a decrease in drag at 15°. All designs, except pyramidical protrusions, increased the lift-to-drag ratio (L/D) performance at 15°. It was found that dimples are better than bumps and spherical features are better than pyramidical ones.